IS BALANCE OF PAYMENTS A MONETARY PHENOMENON? A REVIEW OF EMPIRICAL EVIDENCE - Akpansung, Aniekan O. (EBSU Journal of Social Sciences and Humanities, 2022)
The empirical proofs in this study evidently support the argument that the balance of payments is a monetary phenomenon, and that any disparity in the balance of payments is always necessitated by disturbances in the monetary variables in the countries concerned. Consequently, any observed disequilibrium in a country’s balance of payment can, ceteris paribus, be adroitly corrected via adjustment of domestic credits demand, and hence the size of the foreign trade balance. The monetary authorities can do this by adopting stringent monetary disciplines to limit the growth of domestic credit, so that economic agents will cut back their expenditure relative to their income, so as to rebuild their cash balances.